1999
DOI: 10.1093/emboj/18.14.3956
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid in E-cadherin responsible for host specificity towards the human pathogen Listeria monocytogenes

Abstract: Human E-cadherin promotes entry of the bacterial pathogen Listeria monocytogenes into mammalian cells by interacting with internalin (InlA), a bacterial surface protein. Here we show that mouse E-cadherin, although very similar to human E-cadherin (85% identity), is not a receptor for internalin. By a series of domainswapping and mutagenesis experiments, we identify Pro16 of E-cadherin as a residue critical for specificity: a Pro→Glu substitution in human E-cadherin totally abrogates interaction, whereas a Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
394
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 440 publications
(414 citation statements)
references
References 49 publications
(72 reference statements)
12
394
1
7
Order By: Relevance
“…As previously shown in cells expressing hEcad (Mengaud et al, 1996;Lecuit et al, 1999), the entry of Lm inlA deletion mutant (inlA) was reduced compared with WT Lm in both LS174T and Jar cells (Fig. 4, A and B).…”
Section: Phosphorylation Of Akt Inversely Correlates With Inlb-dependsupporting
confidence: 83%
“…As previously shown in cells expressing hEcad (Mengaud et al, 1996;Lecuit et al, 1999), the entry of Lm inlA deletion mutant (inlA) was reduced compared with WT Lm in both LS174T and Jar cells (Fig. 4, A and B).…”
Section: Phosphorylation Of Akt Inversely Correlates With Inlb-dependsupporting
confidence: 83%
“…In contrast, mouse E-cadherin cannot interact with InlA because the proline is replaced by a glutamic acid residue. 65 The crystal structure of the LRR region of InlA in association with the extracellular domain of human E-cadherin corroborated this observation and revealed that a hydrophobic pocket on the LRR accommodates the E-cadherin proline 16 residue. 66 Oral inoculation of a transgenic mouse model that synthesizes the human E-cadherin in the intestine showed the crucial role of InlA in the crossing of the intestinal epithelium.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 62%
“…Recent studies have demonstrated that L. monocytogenes internalin exhibits decreased association with murine E-cadherin compared with human E-cadherin (43), thereby substantially reducing infection of intestinal epithelial cells. It is possible, therefore, that enteric infection of mice with L. monocytogenes disseminates primarily through M cells lining the small intestine, a route that is believed to be followed by many different enteric bacterial pathogens (44).…”
Section: Discussionmentioning
confidence: 99%